Effect of Dose and Schedule of L-Asparaginase Administration on Early Minimal Residual Disease in Acute Lymphoblastic Leukemia - Gupta, Satyanker; Sehrawat, Amit; Dang, Ketan; Sharma, Lalit; Jaiswal, Sarita; Chakarbarti, Suparno (Indian Journal of Medical and Paediatric Oncology, 2019)
Background and Objectives: L-asparaginase has become the backbone of acute lymphoblastic leukemia induction. In Berlin–Frankfurt–Munster (BFM) 95/2000 protocols, L-asparaginase was given twice weekly for initial 4 weeks. While sufficient L-asparaginase levels are important, there is no apparent correlation between high L-asparaginase levels and minimal residual disease (MRD). In view of toxicities of L-asparaginase, we planned to study the effect of dose and schedule of Escherichia coli-derived L-asparaginase on early MRD by phasing the same total dose, once a week over 8 weeks. Methods: This prospective, observational study enrolled 45 children and young adults ≤40 years. Modified BFM 95 protocol was followed. Weekly 5000 IU/m2 L-asparaginase was given intravenously, and MRD was analyzed at the end of 4 weeks (MRD1) and at 8 weeks (MRD2), using multicolor flow cytometry. MRD positive was defined as residual blasts ≥0.01%. Results: Thirty-one patients were eligible for final analysis. Nine could receive scheduled eight doses of L-asparaginase and 22 patients received less than eight doses. We analyzed age, gender, diagnosis, prednisone response, cytogenetics, central nervous system status, BFM risk group, MRD2, and relapse. L-asparaginase dose association was not statistically significant with respect to MRD2 (P = 0.237). There were no cases of pancreatitis, hypersensitivity, bleeding, or thrombosis. Reasons for patients receiving less than the scheduled eight doses were low serum fibrinogen levels and liver dysfunction. This study revealed 8 MRD1-negative and 13 MRD2-negative patients. Conclusion: L-asparaginase dose intensity does not affect early MRD. Phasing L-asparaginase over 8 weeks could lead to the achievement of more MRD2-negative status and thereby improve long-term outcome. This strategy may also reduce the incidence of adverse drug events.
Keywords: Acute lymphoblastic leukemia; Berlin–Frankfurt–Munster; flow cytometry; L-asparaginase; minimal residual disease